Market-based incentive mechanism for adoption of sustainable production standards throughout rice value chains, in Vietnam - CGIAR Research Program on Rice (2020)
The market-based incentive mechanism was successfully piloted with 199 supermarket shoppers in Can Tho in the Mekong Delta in Vietnam. The methodology and full protocol are published in Food Policy and a follow-up study in Ho Chi Minh City was published in Rural 21.